RELATIONSHIP BETWEEN MALONDIALDEHYDA (MDA) CONDITIONS WITH NEUROTROPIC FACTORS OF FEATURED BRAIN CONTENT (BDNF) ON LANSIA THAT DOES PHYSICAL EXERCISES TERPROGRAM - Yusef Rusdi; Fauziah N Kurdi; Rostika Flora (Sriwijaya University Learning and Education International Conference, 2018)
The purpose of this study was to investigate the relationship between MDA levels and BDNF levels in elderly who performed physical exercise terportgram. This research method uses laboratory experimental research with pree test and post test analysis. The object of research is elderly who are in healthy heart club of branch of sumsel which done in 60 years sempel as much as 20 elderly. Data filing, blood pressure, body tension, weight. MDA levels with TBARS method and BDNF content of information by ELISA method. Spearman rho test results indicate that there is a clear correlation between MDA and BDNF levels with very strong levels in physical exercise (r = 0.06) and (r = 0.42). The conclusion that exists between the levels of Malondialdehyda (MDA) and the Brain Derived Neuronthropic Factor (BDNF) level in the elderly performs preprogrammed physical exercise. This research can be used to train what can improve coqnitive function.